2012
DOI: 10.1185/03007995.2012.746218
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second primary malignancies in patients with treated head and neck cancer: a comprehensive review of literature

Abstract: As a general rule, oral cavity and oropharyngeal squamous cell cancers are associated more with head and neck region SPM, while laryngeal and hypopharyngeal cancers - with that of the lung. As these cancers confer dismal prognosis and shorter survival in patients with HNCs, several literature sources recommend close surveillance for and an aggressive therapy of SPM. Notwithstanding, their optimal management and follow-up schedule remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 57 publications
1
68
0
Order By: Relevance
“…In Europe, the 5-year survival rate varies considerably according to anatomic site, 63.1% for cancer of the larynx, 48.5% for oral cavity, 39.8% for oropharynx and 25.5% for hypopharynx cancer [21]. About 40-60% of HNC patients develop recurrences, and around 20% of HNCs develop second primary cancer (SPC), both being associated with poorer survival [22]. Despite various therapeutic interventions, including surgery, radiotherapy, and chemotherapy, the 5-year survival rate for this disease has improved only marginally during the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the 5-year survival rate varies considerably according to anatomic site, 63.1% for cancer of the larynx, 48.5% for oral cavity, 39.8% for oropharynx and 25.5% for hypopharynx cancer [21]. About 40-60% of HNC patients develop recurrences, and around 20% of HNCs develop second primary cancer (SPC), both being associated with poorer survival [22]. Despite various therapeutic interventions, including surgery, radiotherapy, and chemotherapy, the 5-year survival rate for this disease has improved only marginally during the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of a synchronous lung tumor in these cases is 1%, whereas the incidence of a metachronous tumor increases to 10% in patients who have survived ≥3 years (7,10). When the location of primary malignancies was analyzed in the present study, the second most frequent group was respiratory system malignancies with ten cases (22.2%); laryngeal cancer and lung cancer were included in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Current data wasn't sufficient to evaluate second primary statistically, however it is not easy to obtain sufficient sample of this rare tumor, A systematic review by Atienza, Jonessa Ann S et al [23] reported high incidence of second primaries in head and neck sites, according to them environmental, genetic and immunological factors could explain such association.…”
Section: Discussionmentioning
confidence: 99%